2004
DOI: 10.2175/193864704784131905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Two-Phase Anaerobic Digestion Process for Baltimore's Back River Wastewater Treatment Plant

Abstract: The City of Baltimore, Maryland evaluated the feasibility of converting the conventional high rate (CHR) anaerobic digesters to the two-phase (acid-gas) mesophilic anaerobic digestion process (two-phase process) at its 180-million-gallon per day (MGD) Back River Wastewater Treatment Plant (WWTP) using a dedicated 25-dry ton per day (dtpd) process evaluation facility (PEF). The evaluation of the two-phase process was performed in conjunction with an extensive upgrade of the digestion facilities. The PEF's acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
3
5
0
Order By: Relevance
“…VFA production averaging about 6000 mg/L with an SRT of 1.5-3 days (Ghosh et al 1995) has been reported on digesting WAS only. Similar VFA production was reported (Andryszak et al 2004) with an SRT of 1.5 days when digesting a mixture of TPS (thickened PS) and TWAS (thickened WAS). However, for both cases, the sludge was treated in a fully mixed unit at 368C (compared with 278C in the feedwell).…”
Section: Effect Of Operating Conditions On Vfa Productionsupporting
confidence: 78%
See 1 more Smart Citation
“…VFA production averaging about 6000 mg/L with an SRT of 1.5-3 days (Ghosh et al 1995) has been reported on digesting WAS only. Similar VFA production was reported (Andryszak et al 2004) with an SRT of 1.5 days when digesting a mixture of TPS (thickened PS) and TWAS (thickened WAS). However, for both cases, the sludge was treated in a fully mixed unit at 368C (compared with 278C in the feedwell).…”
Section: Effect Of Operating Conditions On Vfa Productionsupporting
confidence: 78%
“…Similar VFA production was reported (Andryszak et al . ) with an SRT of 1.5 days when digesting a mixture of TPS (thickened PS) and TWAS (thickened WAS). However, for both cases, the sludge was treated in a fully mixed unit at 36°C (compared with 27°C in the feed‐well).…”
Section: Resultsmentioning
confidence: 99%
“…The principal design features of a purpose-built APD are listed below: The objectives of this application are obtaining greater volatile solids loading rates (VSLRs), resulting in a volatile fatty acids (VFAs) concentration range of 5,000 to 10,000 mg/l at the APD discharge, overall median VSr efficiency increase of up to 20 percent, total HRT reduction of up to 20 percent, and increased biogas production. In addition, this application reduces the viscosity of high-thickened solids and therefore improves their transfer characteristics and reduces foaming (Andryszak et al, 2004).…”
Section: Mesophilic Acid Hydrolysis-single Tank Ad Systemmentioning
confidence: 99%
“…Although the methane content of the APD produced biogas ranges between 20 and 30 percent and has higher hydrogen sulfide content than the MPD biogas, the typical combined biogas composition is in the order of 65 percent CH 4 and 35 percent CO 2 with less than 0.1 percent of H 2 S (Andryszak et al, 2004).…”
Section: Mesophilic Acid Hydrolysis-single Tank Ad Systemmentioning
confidence: 99%
“…Acid-methane phased digestion has been used to reduce the risk of toxicity from lipids (Kim et al, 2004) and to accelerate reaction rates and increase VS reduction and process stability by providing the optimal environment for the growth of acid-and methane-producing organisms (Andryszak et al, 2004;Harrison et al, 2005). An important advantage of the phased digestion used to justify implementation at SCBWRF was that the new acid reactors would be designed to handle the high solids concentration feed that could temporarily reach TS concentrations of up to 10% solids and through acid phase sludge hydrolysis, convert the sludge and FOG mix to a less viscous feed to the ESDs that would be easier to mix effectively.…”
Section: Recycled Nutrients From Acid-methane Phased Digestionmentioning
confidence: 99%